Prioritizing Challenges and Strategies for Sustainable Productive Waqf Management in Indonesia: an ANP Method - Fielnanda, Refky (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2025)
Productive waqf management has strong potential to strengthen Islamic social finance and promote regional economic development. However, its implementation remains inefficient, particularly in Jambi, Indonesia. This study examines the key challenges in productive waqf management and proposes strategic solutions to enhance its effectiveness. The Analytic Network Process (ANP) was applied to prioritize challenges and strategies based on expert judgment and interdependent relationships. Data were obtained through in-depth interviews with experts, a focus group discussion, and pairwise-comparison questionnaires. The results indicate that key obstacles include limited managerial capacity at nāẓir, weak institutional governance, particularly the suboptimal role of the Indonesian Waqf Board (BWI) in Jambi, and insufficient government support. The study proposes strategic measures, such as targeted capacity-building for nāẓir, institutional reform, financing integration, and regulatory strengthening to enhance the sustainability of productive waqf governance. Keywords: productive waqf; islamic economics; Analytic Network Process Abstrak Pengelolaan wakaf produktif berpotensi besar memperkuat ekosistem keuangan sosial Islam dan mendorong pembangunan ekonomi daerah. Namun, pelaksanaannya masih belum optimal, khususnya di Jambi, Indonesia. Penelitian ini menganalisis tantangan dalam pengelolaan wakaf produktif dan merumuskan strategi penguatan efektivitas dan keberlanjutannya. Metode Analytic Network Process (ANP) digunakan untuk memprioritaskan tantangan dan strategi berdasarkan penilaian ahli dan keterkaitan antarfaktor. Data diperoleh melalui wawancara mendalam, diskusi kelompok terfokus (FGD), serta kuesioner perbandingan berpasangan. Penelitian ini menemukan kendala utama yang dihadapi meliputi keterbatasan kapasitas manajerial pada nazhir, lemahnya tata kelola kelembagaan, terutama belum optimalnya peran Badan Wakaf Indonesia (BWI) di Jambi, serta minimnya dukungan pemerintah. Penelitian ini merekomendasikan penguatan kapasitas nazhir yang terarah, reformasi kelembagaan, integrasi pembiayaan, dan penguatan regulasi guna meningkatkan keberlanjutan tata kelola wakaf produktif. Kata Kunci: wakaf produktif; ekonomi islam; Analytic Network Process